Salting-out assisted solvent extraction of L (+) lactic acid obtained after fermentation of sugarcane bagasse hydrolysate - Baral, Pratibha; Pundir, Anushka; Kurmi, Akhilesh; Singh, Raghuvir; Kumar, Vinod; Agrawal, Deepti (Elsevier, 2021)
Lactic acid is among the twelve platform chemicals produced from inexpensive and renewable feedstocks such as lignocellulosic biomass. The present study illustrates salting-out assisted solvent extraction of L (+) lactic acid, derived from sugarcane bagasse hydrolysate. Screening studies with various extractants and diluents revealed that a combination of tri-n-butyl phosphate and ethyl acetate yielded the best results and extracted 59.63 ± 1.28% lactic acid from the dilute fermentation broth adjusted to a pH of 1.6 ± 0.2. Various inorganic salts were screened to enhance extraction efficiency further. The addition of 60% (w/v) ammonium sulfate improved the lactic acid extraction by 36.17%. This salt concentration successfully extracted 85.95 ± 0.44% lactic acid to the organic phase under optimized conditions from the fermentation broth at a pH of ~ 2.5 containing 40–100 g L−1 lactic acid. Recovery of > 80% salt is also shown using chilled acetone, which upon reuse showed a nominal decline of 3.3% during extraction. Thus an eco-friendly approach using a green solvent like ethyl acetate with mild operating conditions is demonstrated in the present study.
Keywords: Lactic acid; Sugarcane bagasse hydrolysate; Extraction; Ammonium sulphate; Ethyl acetate; Tri-n-butyl phosphate